Education, Place, and the Sustainability of Rural Communities in Saskatchewan - Terry Wotherspoon (Journal of Research in Rural Education, 1998)
Schools which have long been cornerstones ofsustainability for rural communities are in danger ofdisappearing in many areas that rely on agriculture as the primary industry. Many forecasters project the demise ofrural schooling and the communities the schools serve amidst global pressures to concentrate and centralize economic production, jobs, and services. Other commentators argue that rural schools can playa vital role infostering a sense ofplace that is critical to the development ofmeaningful social, economic, and cultural opportunities in uniquely situated communities. This paper examines the perceptions about schooling's contributions to community sustainability held by southwestern Saskatchewan residents. In the face ofpressures to close and consolidate many community schools, area residents place a high value on the maintenance of extensive local educational services, are generally satisfied with the services available to them, and contribute actively to support schooling. However, schools offer credentials and content that serve urban centres more than local communities. Ifschools are to remain vital to rural community sustainability, educators, policymakers, and community members must offer strategies that link education with the development ofeconomic diversification, meaningful jobs, and supportive community infrastructures.